Development Multimedia Interactive “Menturi” Based on Autoplay to Improve IPAS Learning Outcomes - Nina Armiyati; Sri Sami Asih (Postgraduate, University of Mataram, 2025)
Based on the results of pre-research conducted at SD Negeri Semper Barat 03 Pagi, there are problems found in the lack of interesting, IT-based learning media and the low learning outcomes of students in IPAS subjects. This study aims to develop interactive multimedia ‘menturi’ based on autoplay by innovating by adding handouts at the end of learning material, testing the feasibility of interactive multimedia ‘menturi’ based on autoplay in IPAS learning to improve student learning outcomes, and knowing the effectiveness of using interactive multimedia ‘menturi’ based on autoplay in improving student learning outcomes. This research uses the Borg and Gall development model with only 8 stages. The sample of this research consisted of 31 students of class IV-C SD Negeri Semper Barat 03 Pagi Jakarta. The results showed that; autoplay-based ‘menturi’ interactive multimedia is feasible and effective for use in IPAS learning. It can be seen that the results of validity by material expert validators get a percentage of 93% with very feasible criteria, and media experts get a presentation of 83% with very feasible criteria; The effectiveness of the product can be seen from the results of student responses including small group trials and large group trials with pretest results in small group trials getting an average of 72 and post-test 86, and in large group trials getting an average pretest score of 70 and post-test 80. In the small group trial, the n-gain value was 0.53 with a moderate category, while in the large group trial, the n-gain value was 0.41 with a moderate category. Thus, the results showed that the interactive multimedia ‘menturi’ based on autoplay with the innovation of a handout at the end of the learning material is feasible and effective for use in IPAS learning to improve student learning outcomes.